Electric pulp testing in modern dentistry (LLC "Endo Press", 2020)
Features of fulfillment and interpreting electric pulp test in Russian dentistry discussed. Studied a range of electric pulp testing values of sound teeth and teeth with different dental diseases. The study used a new generation electric pulp test device. Significant fluctuations in individual sensitivity to diagnostic electrical current were recorded.